Preventif Rawat Ulang dengan Pemberdayaan Keluarga dalam Merawat Pasien TB Paru - Sumitro, Sumitro; Suryati, Yayat; Badrujamaludin, Asep (Journal of Telenursing (JOTING), 2023)
This research aims to design a family empowerment module in caring for pulmonary TB patients and experience and family support in caring for pulmonary TB patients. The research method used is qualitative research. The interview results show that the role of family empowerment in the re-treatment of pulmonary TB patients can be seen from seven themes, namely understanding the definition of pulmonary TB, family experience in caring for pulmonary TB patients, actions taken when the family is diagnosed with pulmonary TB, difficulties experienced when caring for patients. Pulmonary TB, the impact felt when treating patients, what will happen if pulmonary TB is not treated immediately, and the family's efforts to ensure that the patient does not relapse or readmission. In conclusion, this research produces a module design for hospitals, patients, and families. Keywords: Family Empowerment, Readmission, Pulmonary TB